On multiplicative (generalized)-$(α,β)$-derivations in prime rings - Garg, Chirag; Sharma, R. K. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 512.5We discuss some algebraic identities related to multiplicative (generalized)-derivations and multiplicative (generalized)-$(α,β)$-derivations on appropriate subsets in prime rings.